Pengaruh E-Wallet, Mobile Banking, dan E-Money Terhadap Transaksi Bisnis Digital Pasca Covid-19 - Afifah Rohmawati; Cris Kuntadi; Rachmat Pramukty (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
In a research or scientific publication, previous or related research is very important. Theories and phenomena of the relationship or influence between variables are strengthened by previous research or related research. This article explores technology-based business transaction research and discusses the elements that influence Post-Covid-19 Digital Business Transactions, namely E-wallets, Mobile Banking, and E-Money. The purpose of this article is to develop hypotheses about how the different variables interact that can be applied to future studies. The findings of the relevant literature evaluation are as follows: 1) E-wallets have an impact on post-Covid-19 digital business transactions; 2) Mobile banking has an impact on post-Covid-19 digital business transactions; and 3) E-Money has an impact on post-Covid-19 digital business transactions.